2021
DOI: 10.2147/rmhp.s290362
|View full text |Cite
|
Sign up to set email alerts
|

Dual Contraceptive Utilization and Associated Factors Among Reproductive-Age Women on Anti-Retroviral Therapy at Hospitals in Central Ethiopia

Abstract: Background Ethiopia is one of the Sub-Saharan African countries with an increasingly risky sexual practice and mostly affected by the Human Immunodeficiency Virus (HIV) epidemic. Dual protection is an important preventive approach which can prevent both unwanted pregnancy and sexually transmitted infections including HIV/AIDS. Therefore, this study aimed to assess the dual contraceptive utilization and associated factors among reproductive-age women on Anti-Retroviral Therapy (ART) in central Ethi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
(19 reference statements)
3
1
0
Order By: Relevance
“…The present study showed that about 71.6% HIV positive women living in rural areas were less likely to use dual contraceptives when compared to their urban counterparts. These findings are similar in line to earlier studies in Ethiopia [22,23]. On the contrary, another study from Northwest Ethiopia reported that urban dwellers use less modern contraceptives when compared to their rural counterparts [24].…”
Section: Discussionsupporting
confidence: 91%
“…The present study showed that about 71.6% HIV positive women living in rural areas were less likely to use dual contraceptives when compared to their urban counterparts. These findings are similar in line to earlier studies in Ethiopia [22,23]. On the contrary, another study from Northwest Ethiopia reported that urban dwellers use less modern contraceptives when compared to their rural counterparts [24].…”
Section: Discussionsupporting
confidence: 91%
“…This finding is in line with a study conducted in Malawi [37]. However, this finding is typically different from the study conducted in the southern part of Ethiopia and Gonder, northern Ethiopia, and West Shoa, Central Ethiopia which revealed that HIV-positive urban women were more likely to use dual contraceptive methods than rural women [19,26,31]. Even if FP knowledge was evenly distributed in all residential areas, women who reside in rural areas show apparently positive behavioral change when counseled frequently by health professionals about the advantage of using dual contraceptive methods, in turn, making them use the method.…”
Section: Discussionsupporting
confidence: 83%
“…This study also revealed the marital status of the women was one of the independent predictors to utilize the dual contraceptive method, respondents who had married were more than 3 times more likely to utilize a dual method of contraceptive when compared to their counterparts. This finding is comparable with finding from West Shoa, Central Ethiopia, Addis Ababa, Southwestern Uganda, Kenya, and Lusaka Zambia [26,[38][39][40][41]. This may be because married women find it simpler to talk about contraception-related issues than single women.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Por el contrario, Tilahun y cols. (25) encontraron que tener entre 15 y 24 años incrementó hasta 8 veces la posibilidad de uso de este tipo de anticoncepción. Este contraste podría evidenciar diferencias en las conductas sexuales de las mujeres de diferentes realidades, con especial consideración en la edad de inicio de relaciones sexuales y el número de parejas sexuales.…”
Section: Discussionunclassified